2019
DOI: 10.1111/1747-0080.12510
|View full text |Cite
|
Sign up to set email alerts
|

Dietitians' perspectives on patient barriers and enablers to weight management: An application of the social‐ecological model

Abstract: Aim Dietitians are nutrition experts who conduct nutrition assessments and provide support to patients seeking to manage their weight. The aim of the present study was to assess dietitians' perspectives on the barriers and enablers encountered by patients during their weight management journey. Methods Fourteen individual semi‐structured interviews were conducted over a 3‐month period in 2017 with dietitians working in Ontario, Canada. All interviews were audio‐recorded and transcribed verbatim. Two researcher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…37 Dieticians in Canada similarly expressed that patients, particularly rural patients and lowincome patients, may encounter access issues with respect to health care and healthy lifestyles. 48 These dieticians highlighted the importance of consistency in messaging among HCPs and stressing small, positive achievements. Koball and colleagues' mixed-method study on American patients who recently saw an internal medical provider noted that the majority of patients of all weights appreciate specific advice and recommendations concerning managing weight through lifestyle changes (diet and exercise).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Dieticians in Canada similarly expressed that patients, particularly rural patients and lowincome patients, may encounter access issues with respect to health care and healthy lifestyles. 48 These dieticians highlighted the importance of consistency in messaging among HCPs and stressing small, positive achievements. Koball and colleagues' mixed-method study on American patients who recently saw an internal medical provider noted that the majority of patients of all weights appreciate specific advice and recommendations concerning managing weight through lifestyle changes (diet and exercise).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the barriers mentioned by participants in the present study and those mentioned by HCPs in previous research extend beyond individual patient encounters to the redressing of structural inequities. 48 There is often an underlying assumption that individuals have access to discretionary time and affordable food and that the only barriers that individuals encounter are easily overcome on an individual, and even internal, level. 50 Higher income also may have a protective effect on the mental health effects of experiencing weight…”
Section: Discussionmentioning
confidence: 99%
“…Further studies, with varied methodology, have found evidence of imbedded biases amongst healthcare providers (Aboueid, Pouliot, Nur, Bourgeault &, Giroux, 2019;Panza et al, 2018;Puhl et al, 2015;Schwartz et al, 2003;Swift, Hanlon, El-Redy, Puhl, & Glazebrook, 2013;Teachman & Brownell, 2001). A study conducted over ten years ago evaluated mock case studies in a sample of college students majoring in nutrition and dietetics and identified moderate amounts of fat phobia, similar to the general public, and various implicit biases towards individuals categorized as overweight and/or obese (e.g.…”
Section: Biases Among Healthcare Providersmentioning
confidence: 99%
“…This review will focus on Canada specifically, as the health care system's funding and policies are unique to Canada. In Canada (2004, it appears research is lacking on RDs' views of weight-related evidence in practice areas other than weight/obesity management (Aboueid et al, 2019;Barr et al, 2004;Chapman et al, 2005;Marchessault et al, 2007).…”
Section: Introductionmentioning
confidence: 99%